Biofield Energy: Emotional Side Effects of Long-term Prescription Drug Use - Bhattessa, Seema (British Journal of Healthcare and Medical Research, 2024)
Mood-altering drugs directly affect the emotional centres of the brain, and though they are meant to stabilise and improve mood, they are also known to induce a range of negative emotional side effects, including depression, anxiety, mania, panic disorder, violence, and suicidality[1]. Somewhat less considered and researched are the emotional side effects of non-mood-altering drugs, particularly those prescribed for chronic illnesses and typically used on a long-term basis. Such emotional side effects may stem from associating the medication with having an “incurable” illness as well as the physiologic effects of the drugs themselves, the latter of which can often be overlooked by both patients and physicians. Some patients who fail to manage their treatment are often faced with a learning curve they must work through to understand their condition and its complexities and treatments. In some cases, the emotional stresses of dealing with chronic illness can manifest in personality changes. Thus, teasing apart chronic illness's complex web of emotions requires a circumspect and nuanced approach.